MAKNA SIMBOL DALAM TRADISI LELANG TEMBAK ANALISIS SEMIOTIKA CHARLES SANDER PIERCE DI DESA SERIDALAM KABUPATEN OGAN ILIR - Putri Citra Hati; Miftah Annisa Kurniati (Universitas Baturaja, 2022)
The shoot auction tradition is a tradition that is carried out during a wedding reception in Seri Dalam Village, Ogan Ilir Regency which has been attached for generations. This study aims to determine the process and meaning of symbols from the shooting auction tradition in the village of Seri Dalam Ogan Ilir. The method used in this study is a qualitative method with a descriptive approach using semiotic analysis from Charles Sander Pierce. This study explains that the wedding reception activity in Seri Dalam Village, Ogan Ilir Regency has a shooting auction culture, namely the bargaining process to get the highest vote or price for the goods offered by the family holding the celebration. The results of the study reveal that in Charles Sander Pierce’s semiotics, it was found that the price auction activity means those who bid with the highest price will be given rewards, namely singing on stage. Goods auctioned in the from of gifts in the from of mukenah, sarong and money. The symbolic meaning of mukenah is that there is a great responsibility as a from of a husband who is ready to teach and guide his wife in matters of religion. While the meaning of the symbol of the sarong is interpreted as covering the genitals in front of the prospective bride. This tradition is held at night aiming to help each other with relatives who are holding a celebration. And this tradition is carried out continously, when the celebration events is over, the family who has carried out the celebration will return the auction as well. Because the purpose of this shooting auction is to ease the burden of the owner’s cost and establish friendship. And the meaning of the symbol of this tradition is an expression of gratitude to Allah SWT. Keywords: Tradition, Shoot Auction, Semiotics Charles Sander Pierce.